Escrita de histórias por crianças de escola pública e escola particular em diferentes situações de produção - Correia, Juliana de Arruda Fraga (2007)
The aim of this study was to verify the progression of wiritten narrative stories made by children from a public and a private school in Recife, in four different production situations: free production, production from engravings presentation, from a told story and from reading of an illustrated book. The work was carried through with 160 children, being 80 of public school and 80 of particular. Each child produced four stories, in a total of 640 stories. The stories had been analyzed and categorized in accordance with the categories of stories proposals by Rego (1985). After the analysis of the results, could be concluded that it had a progression related to the level of text production in function of the teaching advance, clearly seen in private school children. The best situation for public school students was from a told story, while reading of an illustrated book made private school children write more sofisticated stories. There was significant statistics differences between public and private schools in all four situations.